2013
DOI: 10.1111/dote.12056
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of esophageal atresia: review of the research and clinical evidence

Abstract: Esophageal atresia (EA) occurs in one out of 2500 to 4500 live births. As the vast majority of infants are now surviving neonatal corrective surgery, the focus has shifted from mortality to morbidity associated with EA. However, little is known about its psychological morbidity. This paper synthesizes research and clinical evidence to highlight the psychological sequelae of EA, including its impact on parents' psychological functioning and its effects on child development from infancy to adulthood. Whether it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…6 As reported EA survival rates have increased to more than 90% nowadays, 7,8 leading to a shift of attention towards possible long-term morbidities. 9 Previous research on developmental outcome after EA/TEF repair showed normal to impaired motor-and mental development. The impairment was associated with the total anesthesia time.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…6 As reported EA survival rates have increased to more than 90% nowadays, 7,8 leading to a shift of attention towards possible long-term morbidities. 9 Previous research on developmental outcome after EA/TEF repair showed normal to impaired motor-and mental development. The impairment was associated with the total anesthesia time.…”
Section: Introductionmentioning
confidence: 98%
“…Thoracoscopic management is preferred in some hospitals because it provides better visualization of the surgical field, and is associated with less surgical damage and better long‐term outcome with expected lower risk of scoliosis . As reported EA survival rates have increased to more than 90% nowadays, leading to a shift of attention towards possible long‐term morbidities . Previous research on developmental outcome after EA/TEF repair showed normal to impaired motor‐ and mental development.…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, antenatal detection helps future parents to prepare for the birth of an affected infant who will require surgery and intensive care. It also avoids postnatal separation, which can lead to psychological trauma during an important moment for mother‐infant bonding . In the context of an antenatal diagnosis of a fetal digestive abnormality, Aite et al showed that, indeed, there is a positive impact of a multidisciplinary approach on maternal anxiety following both the initial antenatal consultation and the birth .…”
Section: Discussionmentioning
confidence: 99%
“…It also avoids postnatal separation, which can lead to psychological trauma during an important moment for mother-infant bonding. 24 In the context of an antenatal diagnosis of a fetal digestive abnormality, Aite et al showed that, indeed, there is a positive impact of a multidisciplinary approach on maternal anxiety following both the initial antenatal consultation and the birth. 25 survival rate was similar in our sample and appears reassuring compared with older reports.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term respiratory complications including bronchiectasis may result from aspiration, GERD, and chest wall abnormalities [ 104 ]. Both the parents and their neonate are at risk for psychological and traumatic stress (including post-traumatic stress disorder) [ 105 ]. These are long-term issues centered around feeding diffi culties, multiple painful procedures and surgeries, feeding, and airway issues.…”
Section: Surgical Considerationsmentioning
confidence: 99%